EXPLORING THE IMPACT OF PERSON-JOB FIT ON JOB SATISFACTION IN REMOTE WORK SETTINGS: A MODERATION ANALYSIS USING MBTI - Meiny Grace Porajouw; Lilly Linne Kainde (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstrak: This study examines the role of MBTI personality types as moderating variables in the relationship between Person-Job Fit (PJF) and Job Satisfaction (JS). Using a sample of 40 respondents, moderation regression analysis was conducted to test the interaction effects between PJF and four MBTI dimensions (Introversion-Extraversion, Sensing-Intuition, Thinking-Feeling, Judging-Perceiving). The results indicate that PJF has a significant positive effect on JS. The Introversion-Extraversion showed a marginally significant moderating effect (β = -0.346, p = 0.091), suggesting that the PJF-JS relationship is weaker for extraverts. However, the relatively small sample size (N=40) may limit the statistical power to detect moderating effects, particularly for the marginally significant finding. The other three MBTI dimensions did not demonstrate significant moderating effect. Future research with larger, more diverse samples is recommended to verify these preliminary results and explore potential subtle effects of other personality dimensions. This study contributes to the literature by demonstrating that the PJF-JS relationship may be contingent on specific personality characteristics. Keywords: Person-Job Fit, Job Satisfaction, MBTI   Abstrak: This study examines the role of MBTI personality types as moderating variables in the relationship between Person-Job Fit (PJF) and Job Satisfaction (JS). Using a sample of 40 respondents, moderation regression analysis was conducted to test the interaction effects between PJF and four MBTI dimensions (Introversion-Extraversion, Sensing-Intuition, Thinking-Feeling, Judging-Perceiving). The results indicate that PJF has a significant positive effect on JS. The Introversion-Extraversion showed a marginally significant moderating effect (β = -0.346, p = 0.091), suggesting that the PJF-JS relationship is weaker for extraverts. However, the relatively small sample size (N=40) may limit the statistical power to detect moderating effects, particularly for the marginally significant finding. The other three MBTI dimensions did not demonstrate significant moderating effect. Future research with larger, more diverse samples is recommended to verify these preliminary results and explore potential subtle effects of other personality dimensions. This study contributes to the literature by demonstrating that the PJF-JS relationship may be contingent on specific personality characteristics. Kata Kunci: Person-Job Fit, Job Satisfaction, MBTI